“Who will want to know my story?”: Reflecting on decoloniality with adolescents in socioeducation in the light of racial studies: “Who will want to know my story?”: Reflecting on decoloniality with adolescents in socioeducation in the light of racial studies - Peixoto, Ana Clara (2023)
The intention of this writing is to promote the growth of the discussion about decoloniality with teenagers. Based on authors who discuss the topic, we wish to exemplify here, through a lesson plan carried out with adolescent inmates of the Department of Management and Socio-Educational Actions of the State of Rio de Janeiro (DEGASE), how it is emerging to think about a decolonial perspective with adolescents. This work intends to reflect not only on authors who are considered in the field, such as Palermo (1996), but also to bring tensions from Segato (2021) who thinks of coloniality as one of the main tools for the incarceration of the black population. Finally, we intend to show the effects that the approach to the theme had on the conceptions of adolescents who are socio-educational in deprivation of freedom measures, about race, class and gender based on the short story “Rolézim” by writer Geovani Martins (2018). Through the theoretical understanding of these and other authors cited throughout the article, adding practical experience in the classroom, it will be possible to realize that understanding and applying decoloniality in acting as educators and intellectuals, who think about the inequalities present in this society, will make that it is possible to build teachings about intersectionality and racial literacy with marginalized youth in Brazil.